A needs analysis of canoe and kayak slalom to identify a coherent performance analysis strategy - Wells, J.; James, N.; Hughes, M.; Caudrelier, T. (World Congress of Performance Analysis of Sport IX, 2012)
Unlike many individual sports (e.g. running and jumping events in athletics) canoe slalom does not have world records to aim for or to be measured against. This brings challenges to training sessions when determining what was a good performance and how this could be compared with competition performance. Canoe and kayak slalom analysis typically involves identifying time losses / gains by an athlete in comparison to their competitors to identify moves that are quicker and to provide objective feedback to their athlete on how good their performance was. O`Donoghue & Longville (2004) documented a step-by-step procedure of how they developed their notation system for netball. This needs analysis; evolutionary approach was adapted for the current study with the outcome an analysis template that could be used real-time (limited data input) and lapsed-time (additional data input for more complex analysis). As O`Donoghue (2008) stated, it was necessary to have an optimal set of performance indicators to provide sufficient information but small enough to be collected reliably in real-time. Interviews with the coaches and athletes identified the benefits that performance analysis could provide and the performance indicators thought to be beneficial (Table 1). These measures were not simple in many cases, for example split times can be used at different parts of the course and be determined by upstream and downstream gates. Ultimately the utility of these times lay in the ability of the analyst to identify performance standards (peer-related) and quantify differences in times (course specific) with identifiable reasons for the time differentials. The next stage of development hopes to identify season trends e.g. an athlete may lose the majority of time in the upstream gates, with a view to incorporating this information in a coherent performance enhancement strategy.